Forest regeneration under reduced-impact and conventional logging in lowland mixed dipterocarps forest of East Kalimantan, Indonesia - Priyadi, H. (University Putra Malaysia. Tropical Forest Resource Management Program, 2003)
Reduced-impact logging (RIL) trial was carried out in the compartment of operational scale (over 100 ha) in East Kalimantan, Indonesia. Twenty four permanents sample plots (PSPs), of one ha each have been randomly set up for a long term monitoring. All trees (dbh 20 cm) were measured and identified. The objective of this study was to observe how far RIL can reduce logging damage as compared to conventional logging which was done in state-owned company, PT Inhutani, East Kalimantan. Residual stand damage were calculated to be compared with initial density. In conventional logging, the damage which was created in diameter class of 20-50 cm dbh versus felling intensity were recorded as amounting 27% (in low logging intensity), 22% (medium), and 27% (high) from initial density. Meanwhile in diameter class above 50 cm dbh were 3.9% (low) and 6% (both medium and high). In contrast, in reduced-impact logging, residual stand damage in diameter class of 20-50 cm dbh were 10% (low), 20% (medium) and 29% (high). Meanwhile, in diameter class above 50 cm dbh were only 1% (low), 3% (medium) and 6% (high). The study showed the overall density of sapplings of approximately 4,600 stems/ha, which is mainly composed of two families, Euphorbiaceae and dipterocarpaceae. Euphorbiaceae dominated this storey. A total of 705 trees species were recorded from the permanent sample plots, of which 70 trees (9.29%) were dipterocarp species, Dipterocarpus lowlii, D. stellatus, Shorea beccariana, S. brunenscens, S. exelliptica, S. macroptera, S. maxwelliana, S. multiflora, S. parvifolia, S. rubra and S. venulosa. In this study, residual stand damage due to reduced impact and conventional logging with different logging intensity were also be demonstrated.